KEMAMPUAN MENULIS TEKS BERITA MELALUI VIDEO YOUTUBE “KOMPAS TV” SISWA KELAS VIII SMPN 3 SUNGGUMINASA - Agustina Merdekawati Jumatik; Usman Usman; Hajrah Hajrah (Titik Dua: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
Ability to Write News Text via Kompas TV Youtube Video for Class VIII Students of SMPN 3 Sungguminasa. The purpose of this study was to describe the ability to write news text on YouTube Kompas TV videos for Grade VIII students of SMPN 3 Sungguminasa in terms of the structure and language rules of news. This research is a descriptive quantitative research. The method used in the writing test is to measure students' understanding of the main points of the news. The results of the study obtained the average value of the ability to write news text in the structural aspect, namely 70 which was categorized as sufficient. The average value of the ability to write news texts based on rules is 63 which is categorized as sufficient. This shows that the ability to write video news texts for Youtube Kompas TV Class VIII students of SMPN 3 Sungguminasa is in the quite capable category.